Resource Efficiency Strategies and Market Conditions. Issue 2 (April 2015) - Delmas, Magali A.; Pekovic, Sanja
Abstract : In this paper we analyze the factors that drive the adoption of innovative resource efficiency strategies to reduce energy and material use, under different market conditions. We uncover the "paradox" of lower adoption of resource efficiency strategies in an economic downturn and identify the characteristics of firms that adopt these strategies. Using data from a French survey with responses from 5, 877 firms, we show that only 10% of the firms in our sample adopt resource efficiency strategies in perceived economic downturn as compared to 46% in perceived steady or growing market conditions. However, the probability of adopting such strategies in downturn conditions rises to 24% for firms that focus on cost leadership strategies, have adopted environmental standards, conduct their research internally and are vertically integrated. We provide recommendations to encourage more widespread adoption of resource efficiency strategies.